Profil Kadar Kolesterol pada Penderita Hipertensi di Usia Produktif - Gina Nafsa Mutmaina; Astari Nurisani; Sugiah Sugiah; Mamay Mamay; Lia Mar’atiningsih; Meti Rizki Utari; Muhammad Hadi Sulhan; Rismawati Rismawati (Jurnal Siti Rufaidah, 2025)
Hypertension is a chronic clinical condition characterized by persistently elevated blood pressure above normal physiological limits and is a major global health concern due to its strong association with cardiovascular morbidity and mortality. One important contributing factor to hypertension is hypercholesterolemia, or an abnormal increase in total cholesterol levels in the blood. Elevated cholesterol concentrations may accelerate arterial stiffness and increase vascular resistance, thereby worsening blood pressure regulation. This study aimed to describe the relationship between blood pressure status and total cholesterol levels among productive-age individuals diagnosed with hypertension. The study was conducted in July 2023 using a descriptive design. A total of 30 hypertensive respondents within the productive age range were selected through accidental sampling. Data collection involved direct measurement of blood pressure using a sphygmomanometer and assessment of total cholesterol levels through standard clinical procedures. The results showed that the majority of respondents were categorized as having Stage 1 hypertension. With regard to cholesterol profiles, 16 respondents (53%) exhibited normal cholesterol levels, 9 respondents (30%) had borderline high cholesterol levels, and 5 respondents (17%) were classified as having high cholesterol levels. These findings suggest that most hypertensive individuals in the productive age category present with cholesterol levels ranging from normal to borderline high, although a smaller proportion already experience clinically high cholesterol concentrations. The study highlights the importance of regular monitoring of both blood pressure and lipid profiles in productive-age individuals to prevent progression to more severe cardiovascular complications. Lifestyle modification remains a cornerstone in hypertension management, particularly increasing physical activity, adopting a balanced diet low in saturated fats, and maintaining good sleep hygiene. Such preventive strategies can help reduce the dual burden of hypertension and hypercholesterolemia, ultimately lowering the risk of long-term cardiovascular disease.